Suitability of pond sand dilters as safe drinking water solution in storm surge prone areas of Bangladesh: a case study of Post-Aila situation in Shyamnagar, Satkhira district, Khulna - Farhana, Sayeeda (BRAC University, 2012)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2011.